Tinjauan Kritis Implementasi Wasiat Wajibah Beda Agama dalam Hukum Waris Islam di Indonesia - Aco Wahab; Imam Kamaluddin (Ulumul Syar'i : Jurnal Ilmu-Ilmu Hukum dan Syariah, 2023)
This article aims to understand the implementation of mandatory bequests (wasiat wajibah) for interfaith heirs in Indonesia and the arguments supporting it, as well as critique the implementation. This study is a library research using a qualitative approach. Primary data sources were obtained from the Supreme Court of Indonesia’s decision No. 368.K/AG/1995, related decisions, and the Compilation of Islamic Law. The implementation of mandatory bequests in Indonesia has experienced an expansion of meaning as seen in the Supreme Court's decision No. 368.K/AG/1995, which grants inheritance to interfaith heirs through mandatory bequests. This decision has subsequently become jurisprudence used by judges in resolving similar cases. The decision aims to ensure the welfare of all heirs; however, it contradicts the hadith prohibiting inheritance between people of different religions. Moreover, the Supreme Court’s decision allows interfaith heirs to receive inheritance through mandatory bequests, leading to the perception that religious differences are not a barrier to obtaining inheritance